Transformation of the GDP Structure under Post-Industrial Economic Development (Uzbekistan Open Conference, 2025)
The article examines the transformation of the GDP structure in the context of post-industrial economic development. It analyzes the key trends of the transition from an industrial model to a knowledge-based economy, the expansion of the service sector, and the growing importance of intangible assets and technological innovation. Special attention is given to the role of digitalization, human capital, and innovation infrastructure in shaping value added. Based on international experience, the study highlights major structural changes and assesses the prospects and challenges for developing countries, including Uzbekistan.